Immigrant health access in Texas: policy, rhetoric, and fear in the Trump era - Timothy Callaghan; David J. Washburn; Katharine Nimmons; Delia Duchicela; Anoop Gurram; James Burdine (BMC, 2019)
Abstract Background Since the 2016 presidential election, reports have suggested that President Trump's rhetoric and his administration's proposed policies could be exacerbating barriers to accessing health care for undocumented as well as lawfully present immigrants and their families in the United States. However, very little empirical work has analyzed this possibility or detailed how these reports and rhetoric have altered the health seeking behavior of mixed immigration status families. Methods Using a series of focus groups throughout Texas in both English and Spanish, this qualitative study analyzes changes to health access for immigrants. We consulted Community Health Workers to better understand the barriers encountered by their otherwise hard-to-reach undocumented clients and their families as they interface with the health system, revealing key insights about the changing nature of barriers to access under the Trump administration. Results We identify four key themes about the changing nature of immigrant health access in the United States: growing fear of interacting with health and social services; that social networks are paradoxically limiting health access in the current political climate; that the administration's rhetoric and proposed policies are impeding health seeking behavior; and that children are encountering new barriers to social program participation. Conclusions The Trump administration, its proposed immigration policies, and his rhetoric are posing new and significant barriers to health access for immigrants and their families.